In vivo imaging of Α7 nicotinic receptors as a novel method to monitor neuroinflammation after cerebral ischemia. Issue 8 (12th March 2018) - Colás, Lorena; Domercq, Maria; Ramos‐Cabrer, Pedro; Palma, Ana; Gómez‐Vallejo, Vanessa; Padro, Daniel; Plaza‐García, Sandra; Pulagam, Krishna R.; Higuchi, Makoto; Matute, Carlos; Llop, Jordi; Martín, Abraham
Abstract: In vivo positron emission tomography (PET) imaging of nicotinic acetylcholine receptors (nAChRs) is a promising tool for the imaging evaluation of neurologic and neurodegenerative diseases. However, the role of α7 nAChRs after brain diseases such as cerebral ischemia and its involvement in inflammatory reaction is still largely unknown. In vivo and ex vivo evaluation of α7 nAChRs expression after transient middle cerebral artery occlusion (MCAO) was carried out using PET imaging with [ 11 C]NS14492 and immunohistochemistry (IHC). Pharmacological activation of α7 receptors was evaluated with magnetic resonance imaging (MRI), [ 18 F]DPA‐714 PET, IHC, real time polymerase chain reaction (qPCR) and neurofunctional studies. In the ischemic territory, [ 11 C]NS14492 signal and IHC showed an expression increase of α7 receptors in microglia and astrocytes after cerebral ischemia. The role played by α7 receptors on neuroinflammation was supported by the decrease of [ 18 F]DPA‐714 binding in ischemic rats treated with the α7 agonist PHA 568487 at day 7 after MCAO. Moreover, compared with non‐treated MCAO rats, PHA‐treated ischemic rats showed a significant reduction of the cerebral infarct volumes and an improvement of the neurologic outcome. PHA treatment significantly reduced the expression of leukocyte infiltration molecules in MCAO rats and in endothelial cells after in vitro ischemia. Despite that, the activation of α7 nAChR had no influence to the blood brain barrier (BBB) permeability measured by MRI. Taken together, these results suggest that the nicotinic α7 nAChRs play a key role in the inflammatory reaction and the leukocyte recruitment following cerebral ischemia in rats. Main Points: This imaging study shows the expression of α7 nAChRs on glial cells after stroke in rats. The modulation of α7 expression decreases inflammation, reduces leukocyte infiltration and improves the brain injury after cerebral ischemia.